Edukasi Bahaya Sampah Plastik pada Perairan dan Biota Laut di Sekolah Alam, Pantai Bajulmati, Kabupaten Malang, Jawa Timur - Dian Aliviyanti; Rarasrum Dyah Kasitowati; Defri Yona; Bambang Semedi; Rudianto Rudianto; Muhammad Arif Asadi; Andik Isdianto; Citra Satrya Utama Dewi (Abdi Geomedisains, 2022)
Plastic is one of the most common pollutants found in marine waters. The direct negative impact of plastic waste on marine organisms is causing blockages in the digestive tract if eaten either intentionally or unintentionally. One of the efforts to reduce plastic waste is to build public awareness and readiness to actively participate in solving the problem of plastic waste. Therefore, Marine Science Study Program, FFMS, Universitas Brawijaya is dedicated to provide education about the dangers of plastic waste for aquatic communities and marine biota at a pioneering nature school for the Bajulmati Sea Turtle Conservation (BSTC) community in Bajulmati Beach, Malang Regency, East Java. In general, community service activities take place in online and offline manner. The educational methods given to students are a participatory and collaborative learning method, namely by providing an understanding of the material through class discussions and practical waste sorting activities in the field. The results of educational activities on the dangers of plastic waste can increase public knowledge and awareness, especially students at the BSTC nature school so that later it will have an effect on wiser plastic use behavior. Through this activity, it is expected that the resulted knowledge and awareness can foster a sense of love for the environment and can also affect a better use of plastic.